2020
DOI: 10.1542/hpeds.2019-0092
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Social Determinants of Health in Hospitalized Children

Abstract: Outpatient screening for social determinants of health (SDH) improves patient access to resources. However, no studies have examined if and how inpatient pediatric providers perform SDH screening. We aimed to identify inpatient pediatric provider screening practices for SDH, barriers to screening, and the acceptability of screening for hospitalized patients. METHODS: We conducted a multicenter descriptive study at 4 children's hospitals surveying inpatient hospitalists and nurses on the general wards about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…This is an approach gaining traction in healthcare settings. 36 Social workers or others with skills in care coordination or patient navigation can then help connect individuals with the necessary resources that are available on their campus and in their community. Such an approach is broadly consistent with evidence in other domains about the benefits of intervening on contextual factors that shape primary routines in times of stress.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…This is an approach gaining traction in healthcare settings. 36 Social workers or others with skills in care coordination or patient navigation can then help connect individuals with the necessary resources that are available on their campus and in their community. Such an approach is broadly consistent with evidence in other domains about the benefits of intervening on contextual factors that shape primary routines in times of stress.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Despite a study reporting that only 38% of pediatric hospitals perform inpatient transition initiatives [15], we found that transition-specific interventions during hospitalization were possible, including administration of the TRAQ and providing education, instruction, and goal-setting based on responses. Similarly, although SDHs are rarely screened for during hospitalization, we were able to implement screening on our patients [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In primary care and emergency department settings, [16][17][18][19] SDoH screening is often performed by medical assistants, medical students, or nurses early during a patient encounter; a positive screen generates an electronic health record (EHR) order set visible to a provider, who then provides a patient with appropriate community resources and referrals. Previous models have suggested that screening tools should be integrated into the EHR [16][17][18][19][20] and screening should be made a formal part of the patient registration or rooming process, with tasks assigned to a specific care team member. 19 At this time, food insecurity screening is less established in hospital settings compared to ambulatory care settings.…”
Section: Introductionmentioning
confidence: 99%